AKTIVITAS AMILUM BENGKUANG (Pachyrrizus erosus (L.) Urban) SEBAGAI TABIR SURYA PADA MENCIT DAN PENGARUH KENAIKAN KADARNYA TERHADAP VISKOSITAS SEDIAAN - Zulkarnain, A. Karim; Ernawati, Novi; Sukardani, Nurul Ikka (Majalah Obat Tradisional, 2013)
Yam starch (Pachyrhizus erosus (L.) Urb.) with microparticles of size and had opaque properties could be used as an physical sunscreens. Yam starch was made in creams and lotions formulation and applied topically. This study aimed to determine the effect of yam starch concentration to the increasing of creams and lotions formulation as well as sunscreens activity in mice seen from its Sun Protecting Factor (SPF). Yam starch was obtained by the deposition method, then was done characterization and measurement of particle diameter. The formulation of creams and lotions each in 3 formulas with yam starch concentration of 15%, 20%, and 25%, further the viscosity and physical stability were observed under extreme heat and cold conditions. The observations during storage were colour, odor, homogenity, and viscosity. Sunscreen activity was determined by in vivo method using Swiss Webster female mice strains induced by 8-MOP, and then observation of its SPF value. The viscosity data in extreme hot and cold conditions was analyzed statistically at significance level of 95%. The results showed that the more increase of the concentration of yam starch the more increase of viscosity, while the colour, odor, and homogenity of the formulation did not change during storage. Creams and lotions formulation with starch concentration of 15%, 20%, and 25%, had sunscreen activity in vivo in mice, with SPF value of 1.22; 1.52, and 2.38.